Carbohydrate supplementation increases intramyocellular lipid stores in elite runners - Sousa, M.; Simoes, H. G.; Campi de Castro, C.; Garcia Otaduy, M. C.; Negrao, C. E.; Rodrigues Pereira, R. M.; Madsen, K.; Rossi da Silva, M. E. (Metabolism, 2012)
The objective was to determine the effects of carbohydrate (CHO) supplementation on exercise-induced hormone responses and post-training intramyocellular lipid stores (IMCL). Twenty-four elite male athletes (28.0±1.2 years) were randomized to receive CHO (maltodextrin solution) or zero energy placebo solution (control group). The high-intensity running protocol consisted of 10×800 m at 100% of the best 3000-m speed (Vm3 km) and 2×1000 m maximal bouts in the morning and a submaximal 10-km continuous easy running in the afternoon of day 9. IMCL concentrations were assessed by 1H-MRS before (-day 9) and after training (day 9) in soleus (SO) and tibialis anterior (TA) muscles. Blood hormones were also measured before, during, and post-exercise. The percent change (?%) in TA-IMCL was higher in the CHO group (47.9±24.5 IMCL/Cr) than in the control group (-1.7±13.1, respectively) (P=.04). Insulin concentrations were higher in the CHO group post-intermittent running compared to control (P=.02). Circulating levels of free fatty acids and GH were lower in the CHO group (P>.01). The decline in performance in the 2nd 1000-m bout was also attenuated in this group compared to control (P<.001 and P=.0035, respectively). The hormonal milieu (higher insulin and lower GH levels) in the CHO group, together with unchanged free fatty acid levels, probably contributed to the increased IMCL stores. This greater energy storage capacity may have improved post-exercise recovery and thus prevented performance deterioration.